2021
DOI: 10.1111/jbg.12650
|View full text |Cite
|
Sign up to set email alerts
|

A breeding program for Nile tilapia in Brazil: Results from nine generations of selection to increase the growth rate in cages

Abstract: Genetic improvement has the potential to improve the productivity of a trait under selection; furthermore, the benefits are permanent, sustainable, and cumulative over generations (Gjedrem, 2012). Quantitative genetics and selective breeding are powerful tools to increase commercial production and have achieved substantial productivity improvements for fishes and shellfishes (Gjedrem & Rye, 2018). Genetic improvement in the animals can suggest an increase in the farm profit, and when breeding is highly special… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…In this study, we studied the genetic parameters of body weight, body length, and tail length traits and found that the h 2 R values of body weight trait were low (60 and 120 days), but the h 2 R value was moderate at 90 days, and the mean values of realized heritability of the three morphological traits were at moderate level. Similarly, in many Perciformes fish, the h 2 R of body weight trait ranged from 0.20 to 0.53 (Nguyen Huu et al, 2014;Garcia et al, 2017;Yoshida et al, 2021;Gonzalez et al, 2022), and most of them were at moderate level. Moderate and high heritability on the traits demonstrates promising effects on genetic improvement in specific selective breeding programs, and improvement of the traits would be achieved through selection (Gjedrem and Baranski, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we studied the genetic parameters of body weight, body length, and tail length traits and found that the h 2 R values of body weight trait were low (60 and 120 days), but the h 2 R value was moderate at 90 days, and the mean values of realized heritability of the three morphological traits were at moderate level. Similarly, in many Perciformes fish, the h 2 R of body weight trait ranged from 0.20 to 0.53 (Nguyen Huu et al, 2014;Garcia et al, 2017;Yoshida et al, 2021;Gonzalez et al, 2022), and most of them were at moderate level. Moderate and high heritability on the traits demonstrates promising effects on genetic improvement in specific selective breeding programs, and improvement of the traits would be achieved through selection (Gjedrem and Baranski, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, adding pedigree records to the program made it possible to implement optimal contributions selection to minimize short-term inbreeding and associated inbreeding depression and long-term loss of allelic diversity over generations (Knibb et al, 2014). Similar family/nucleus-based strategies have been implemented in the GIFT tilapia breeding program in Philippines, producing a cumulative response of 67% improvement of growth rate over five generations in pond culture (Bentsen et al, 2017), in Nile tilapia in freshwater cages in Brazil producing 4% genetic gain per generation after five generations of selection , and in freshwater cages in Brazil producing around 3.3% gain in daily weight gain after nine generations of selection (Yoshida et al, 2022).…”
Section: Acknowledgementsmentioning
confidence: 96%
“…Dissemination from central nucleus breeding programs may require comprehensive arrangements and management between several institutions (Tayamen, 2004), In central nucleus breeding programs, the candidates' performances are measured in the central location with performance of relatives in test stations incorporated in a selection index. Test stations are used to phenotype for di cultto-measure traits on siblings of the candidates, such as slaughterhouses for carcass traits (Prchal et al, 2020), containment facilities for disease challenge tests (Ødegård et al, 2006), or commercial production environments for production traits (Yoshida et al, 2022). Central-nucleus breeding programs are commonly used by breeding companies whose business is mainly aimed at selling genetically improved material (eggs or fingerlings) rather than profiting Bio-secure nucleus facility Broodstock directly from harvested fish or fish products.…”
Section: Breeding Program Designs 121 Central Nucleus Breeding Programsmentioning
confidence: 99%